Frequency of IDH1 mutation in adult-type diffuse astrocytic gliomas in a tertiary hospital in Kenya - Gakinya, Samuel; Mutuiri, Anderson; Onyuma, Timothy; Cheserem, Beverly; Mogere, Edwin (Frontiers in Medicine, 2024)
The 2021 WHO classification of gliomas has separated gliomas based on their IDH mutation status reflecting differences in their pathogenesis and clinical characteristics. There is paucity of data on the prevalence of IDH mutations in gliomas from this region. This study aimed at determining the frequency of IDH1 mutation in adult type diffuse astrocytic gliomas in a tertiary hospital in Kenya. Approximately half of the gliomas were positive for IDH1 mutation with a slight male predominance. Our study provides crucial insights on the frequency of IDH1 mutations in gliomas in Kenya.